2014
DOI: 10.1097/lbr.0000000000000094
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-9 Expression in Lung Cancer Patients and Its Relation to Serum MMP-9 Activity, Pathologic Type, and Prognosis

Abstract: The expression and activity of MMP-9 are upregulated in NSCLC and are related to the pathologic type and clinical stage of NSCLC. Significantly higher expression and activity of MMP-9 in tumor tissue than in the surrounding tissue supports the important role of this metalloproteinase in the growth of lung cancer, and it could be used as a suggested therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 23 publications
(17 reference statements)
4
41
0
1
Order By: Relevance
“…MMP-9 is involved in basement membrane degradation that furthers tumor invasion and metastases [42]. Past studies showed that MMP-9 s are highly elevated in LC patients, especially stage III-IV [43,44]. We also observed a correlation between IL-8 and MMP-9 levels in LC patients.…”
Section: Discussionsupporting
confidence: 61%
“…MMP-9 is involved in basement membrane degradation that furthers tumor invasion and metastases [42]. Past studies showed that MMP-9 s are highly elevated in LC patients, especially stage III-IV [43,44]. We also observed a correlation between IL-8 and MMP-9 levels in LC patients.…”
Section: Discussionsupporting
confidence: 61%
“…Enhanced expression and upgraded activity of MMP-2 and -9 resulted in degradation of extracellular matrix and destruction of basilar membrane, which facilitated the migration of cancer cells (26,27). On the contrary, restricted expression of MMP-2 and -9 in cancer cells leads to a better prognosis (28)(29)(30). The results from the present study showed that exposure of NSCLC H520 cells to phloretin led to decreased invasion and migratory ability.…”
Section: Discussionsupporting
confidence: 55%
“…In addition to lung cancer, other cancers such as breast cancer exhibit high expression of MMP9 (38)(39)(40). MMP9 is associated with pathological type, and positive immunostaining for MMP9 has prognostic value for the distant metastasis or local recurrence of lung cancer (17,41,42). VEGF has been reported to induce tumor blood vessel proliferation and possibly contributes to the extravasation of cancer cells and the formation of metastasis (43).…”
Section: Discussionmentioning
confidence: 99%